2020
DOI: 10.1063/5.0023593
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining formation efficiencies of one-electron-reduced species of redox photosensitizers

Abstract: Improvement in the photochemical formation efficiency of one-electron-reduced species (OERS) of a photoredox photosensitizer (a redox catalyst) is directly linked to the improvement in efficiencies of the various photocatalytic reactions themselves. We investigated the primary processes of a photochemical reduction of two series [Ru(diimine)3]2+ and [Os(diimine)3]2+ as frequently used redox photosensitizers (PS2+), by 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole (BIH) as a typical reductant in detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…As exhibited in Figure b, the EAS obtained from the fits clearly show that the 3 MLCT state (A, 3 [Ir + -BL – ]-Re ) evolves into the IET state (B, Ir + -[BL-Re] – ) followed by an additional C state appearing on a slower time scale of 1.2–1.4 ns (Figure b). Note that the evolutions of EAS for A → B and its time constants are similar to those observed in the TA spectra of Ir-BL-Re (Figure b), except that more intense and broad absorption appears near >600 nm in the TA spectra of the Ir-BL-Re + BIH samples, presumably due to the absorption of BIH radicals generated by pump pulse . This indicates that the same IET process occurs in the presence of BIH.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…As exhibited in Figure b, the EAS obtained from the fits clearly show that the 3 MLCT state (A, 3 [Ir + -BL – ]-Re ) evolves into the IET state (B, Ir + -[BL-Re] – ) followed by an additional C state appearing on a slower time scale of 1.2–1.4 ns (Figure b). Note that the evolutions of EAS for A → B and its time constants are similar to those observed in the TA spectra of Ir-BL-Re (Figure b), except that more intense and broad absorption appears near >600 nm in the TA spectra of the Ir-BL-Re + BIH samples, presumably due to the absorption of BIH radicals generated by pump pulse . This indicates that the same IET process occurs in the presence of BIH.…”
supporting
confidence: 69%
“…Note that the evolutions of EAS for A → B and its time constants are similar to those observed in the TA spectra of Ir-BL-Re (Figure 2b), except that more intense and broad absorption appears near >600 nm in the TA spectra of the Ir-BL-Re + BIH samples, presumably due to the absorption of BIH radicals generated by pump pulse. 29 This indicates that the same IET process occurs in the presence of BIH.…”
mentioning
confidence: 84%
“…We reported that the higher quantum yield of photochemical formation of the OERS of [Ru(X 2 bpy) 3 ] 2+ and [Os(X 2 bpy) 3 ] 2+ (X 2 bpy = 4,4′-X 2 -2,2′-bipyridine) using an electron donor was obtained using the complex with higher oxidation power in the excited state. 16 It was proposed that the stronger oxidation power of the excited complex should induce longer distance between the reduced complex and the oxidized electron donor in a solvent cage, which can suppress the speed of the backelectron transfer reaction. We can assume that the stronger oxidation power of the excited Cu2CF 3 ph than those of Cu2Hph and Cu2Bph, which is supported by the fact that the quenching rate constant k q is larger in the case of Cu2CF 3 ph than those of the others (Table 1), caused the highest quantum yield of formation of the OERS of Cu2CF 3 ph in these three complexes as well.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although we have not been able to clarify the reason, yet, we can propose one possible reason: the strongest oxidation power of the excited state of Cu2CF 3 ph . We reported that the higher quantum yield of photochemical formation of the OERS of [Ru­(X 2 bpy) 3 ] 2+ and [Os­(X 2 bpy) 3 ] 2+ (X 2 bpy = 4,4′-X 2 -2,2′-bipyridine) using an electron donor was obtained using the complex with higher oxidation power in the excited state . It was proposed that the stronger oxidation power of the excited complex should induce longer distance between the reduced complex and the oxidized electron donor in a solvent cage, which can suppress the speed of the back-electron transfer reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to photoredox catalysis, the M À generation is important for many photochemical carbon dioxide reduction [12,[81][82][83] and hydrogen production [13,[84][85][86][87][88][89][90][91][92] mechanisms, demonstrating that the new mechanism introduced in this manuscript has severalp ossible application areas. Our study on the heavily underexplored inherente ffi-ciency of photoinduced electron transfer events might trigger furtherq uantitative investigations that could contribute to a better understanding of how to use photons moree fficiently, [93] which could ultimately result in more sustainability in photochemistry. [94] Elucidating the interplay of spin states, heavy atom effects and inherentr eaction (rather than emission quenching) efficienciess hould therefore be very important for the photochemistry of the future.…”
Section: Discussionmentioning
confidence: 98%